2018
DOI: 10.3748/wjg.v24.i13.1440
|View full text |Cite
|
Sign up to set email alerts
|

Mild drinking habit is a risk factor for hepatocarcinogenesis in non-alcoholic fatty liver disease with advanced fibrosis

Abstract: AIMThe impact of mild drinking habit (less than 20 g/d of ethanol) on the clinical course of non-alcoholic fatty liver disease (NAFLD) has not been determined. We examined the influence of a mild drinking habit on liver carcinogenesis from NAFLD.METHODSA total of 301 patients who had been diagnosed as having NAFLD by liver biopsy between 2003 and 2016 [median age: 56 years, 45% male, 56% with non-alcoholic steatohepatitis, 26% with advanced fibrosis (F3-4)] were divided into the mild drinking group with ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 38 publications
0
79
0
Order By: Relevance
“…Although both studies evaluated lifetime drinking and made careful efforts to exclude previous drinkers and binge drinkers and adjusted for multiple confounders, the cross‐sectional study by Dunn and colleagues () found protective effects of low alcohol use, whereas the longitudinal study by Ajmera and colleagues () reported harmful effects. Similarly, although low alcohol use has been found protective from steatosis in numerous cross‐sectional Japanese studies, the only longitudinal ones reported increased HCC risk (Kawamura et al, ; Kimura et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although both studies evaluated lifetime drinking and made careful efforts to exclude previous drinkers and binge drinkers and adjusted for multiple confounders, the cross‐sectional study by Dunn and colleagues () found protective effects of low alcohol use, whereas the longitudinal study by Ajmera and colleagues () reported harmful effects. Similarly, although low alcohol use has been found protective from steatosis in numerous cross‐sectional Japanese studies, the only longitudinal ones reported increased HCC risk (Kawamura et al, ; Kimura et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Vilar‐Gomez and colleagues () found that, in patients with NAFLD cirrhosis, low alcohol use (<30 g/d for men and <20 g/d for women) was associated with an increased risk of death or liver transplantation (hazard ratio 2.3), hepatic decompensation (hazard ratio 1.7), and HCC (hazard ratio 3.2) compared to abstinence, a finding that reinforces the need for absolute alcohol abstinence in patients with cirrhosis. Two additional studies found an increased risk for HCC among NAFLD patients with advanced fibrosis or cirrhosis reporting any alcohol use (Ascha et al, ; Kimura et al, ).…”
Section: Low Alcohol Intake In the Presence Of Nafld And/or Metabolicmentioning
confidence: 99%
“…HCC is a leading cause of cancer mortality, with poor prognosis and very few effective therapeutic options. Risk factors for HCC include persistent infection with hepatitis B and C viruses, obesity, metabolic syndrome, nonalcoholic steatohepatitis, alcohol consumption, exposure to aflatoxins, and inborn errors of metabolism, such as α‐1 antitrypsin deficiency, tyrosinemia, and citrin deficiency . Recently, gut microbiota and BAs were also shown to be associated with HCC development …”
mentioning
confidence: 99%
“…Other glucose‐lowering agents had already been administered in three patients. Non‐alcoholic steatohepatitis was suspected based on the criteria of: (i) the presence of hepatorenal contrast and increased hepatic echogenicity on abdominal ultrasonography; (ii) ethanol consumption of <20 g/day; (iii) the absence of other causes of liver dysfunction, such as viral hepatitis, drug‐induced liver injury, autoimmune liver diseases, primary sclerosing cholangitis, Wilson disease, hereditary hemochromatosis, and citrin deficiency; and (iv) histologically confirmed using biopsied specimens. Body weight (BW) and height were measured before liver biopsy in a fasting state.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of obesity was defined as a body mass index (BMI) >25 kg/m 2 according to criteria released by the Japan Society for the Study of Obesity. Clinical information was also recorded, with the presence of hypertension and hyperlipidemia being evaluated as described previously …”
Section: Methodsmentioning
confidence: 99%